2016
DOI: 10.3892/mmr.2016.4951
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of epidermal growth factor receptor family receptors and ligands in a mutant K-ras group of patients with colorectal cancer

Abstract: Abstract. The present study investigated the expression profiles of the epidermal growth factor receptor (EGFR) family, which consists of four transmembrane tyrosine kinase receptors and their eight ligands, in 122 patients with colorectal cancer (CRC) using reverse transcription-quantitative polymerase chain reaction analysis. On comparison of the CRC primary tumor and matched adjacent normal mucosa (ANM) tissue samples, the mRNA expression levels of ErbB3, but not ErbB1, were significantly increased in CRC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The total expression level of each EGFR ligand (nM) did not show any significant association with KRAS mutations as evaluated by ELISA (Table S1 and Figure S2). Notably, consistent with previous reports [30,31], we found that KRAS -mutant PDXs tended to show significantly higher fractions of high-affinity EGFR ligands and lower fractions of low-affinity EGFR ligands (Figure 2A,B), in addition to a higher ratio of high- to low-affinity EGFR ligands, than did the KRAS wild-type PDXs (Figure 2C,D). This indicates that the distribution of high- and low-affinity EGFR ligands depends on the presence of a KRAS mutation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The total expression level of each EGFR ligand (nM) did not show any significant association with KRAS mutations as evaluated by ELISA (Table S1 and Figure S2). Notably, consistent with previous reports [30,31], we found that KRAS -mutant PDXs tended to show significantly higher fractions of high-affinity EGFR ligands and lower fractions of low-affinity EGFR ligands (Figure 2A,B), in addition to a higher ratio of high- to low-affinity EGFR ligands, than did the KRAS wild-type PDXs (Figure 2C,D). This indicates that the distribution of high- and low-affinity EGFR ligands depends on the presence of a KRAS mutation.…”
Section: Resultssupporting
confidence: 92%
“…Low expression levels of AREG and EREG associated with KRAS mutations might indicate a tumor that is less dependent on EGFR and is therefore particularly prone to developing resistance to anti-EGFR MoAbs [6,8,10,20,21]. Moreover, the expression levels of AREG and EREG were found to be significantly decreased in mutant- KRAS cases, compared to those in the wild-type cases [30]. Sustained extracellular signal–regulated kinases (ERK) signaling mediated by KRAS mutations was shown to boost secretion of the high-affinity EGFR ligands HB-EGF and TGF-α, which in turn activated EGFR in an autocrine fashion [31].…”
Section: Resultsmentioning
confidence: 99%
“…The tumor heterogeneity is partially determined by the differences in biomarkers. In this study, we only studied p53 as one possible microscopical prognostic marker which could be considered as a limitation of this study, but the incidence of other biological marker abnormalities, including K-ras, 25 BRAF, 26 DNA mismatch repair (MMR), 27 changed much less than p53. Furthermore, we excluded several macroscopical factors that would have influenced results, and we had a longer median follow-up.…”
Section: Discussionmentioning
confidence: 99%
“… 53 NRG2 ligand binds with ErbB2 receptors and downstream signaling lead to colorectal cancer and breast cancer progression. 54 , 55 Potential role of Keratin 5 (KRT5) as well as Collagen, type IV, alpha 3 (COL4A3) in invasive metastasis and disease recurrence in ovarian cancer have also been previously known. 56 , 57 Although a defined role for PANX1 in ovarian cancer is thus far unknown, it is shown to promote invasive migration in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%